2020
DOI: 10.3389/fphar.2020.01158
|View full text |Cite
|
Sign up to set email alerts
|

Luteoloside Exerts Analgesic Effect in a Complete Freund’s Adjuvant-Induced Inflammatory Model via Inhibiting Interleukin-1β Expression and Macrophage/Microglia Activation

Abstract: Background: Flavonoid monomers are proved to have an anti-inflammatory effect and may also be promising for chronic pain treatment. In the present study, the analgesic effect and the relevant mechanisms of luteoloside, one of the flavonoid monomers, were investigated. Methods: The analgesic effect of luteoloside was first evaluated in complete Freud's adjuvant induced inflammatory model by von Frey test and Hargreaves test in both male and female mice. The interleukin-1b levels in plantar tissue, serum, dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Luteoloside, a type of flavonoid glycoside, can be isolated from the plant Lonicera japonica ( Xiong et al, 2013 ; Lin et al, 2019 ; Shi et al, 2020 ). It has recently been reported to possess anti-inflammatory and antibacterial properties.…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%
“…Luteoloside, a type of flavonoid glycoside, can be isolated from the plant Lonicera japonica ( Xiong et al, 2013 ; Lin et al, 2019 ; Shi et al, 2020 ). It has recently been reported to possess anti-inflammatory and antibacterial properties.…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%
“…Botulinum toxin type A can hinder the sensitization of microglia and the release of TNF-α by controlling the sensitization of P2X4 receptors and P38 MAPK signaling pathways in spinal cord microglia, thus easing neuroinflammation in chronic inflammatory pain . Formononetin and Luteolin have anti-inflammatory, analgesic, and inhibitory effects on microglial activation. , …”
Section: Glial Cells In the Central Nervous System And Inflammatory Painmentioning
confidence: 99%
“…34 Formononetin and Luteolin have anti-inflammatory, analgesic, and inhibitory effects on microglial activation. 35,36 2.2. Astrocyte.…”
Section: Glial Cells In the Central Nervous Systemmentioning
confidence: 99%
“…Zhang et al [101] reported that, under TBHPmediated oxidative stress, NRG promotes autophagy in rat NP cells by activating the AMPK signalling pathway, which inhibits cell apoptosis and increases the production of collagen II and aggrecan. Gao et al [102] found that NRG can substantially reduce the expression of inflammatory cytokines TNF-α and IL-6; it can improve the matrix [112]. Lut exerts antioxidant, anti-inflammatory, antiautophagy, and analgesic effects [113].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Luteoloside (Lut) is a natural flavonoid of honeysuckle, lettuce, silver flower, and salvia [ 112 ]. Lut exerts antioxidant, anti-inflammatory, antiautophagy, and analgesic effects [ 113 ].…”
Section: Natural Pharmacological Productsmentioning
confidence: 99%